Fog and Haze Removal Based on Image DeHazing Technique - B, Naveen; P, Bharath Kumar Chowdary (International Journal of Computer Sciences and Engineering, 2019)
Image dehazing is a technique to improve the images picked up in poor climate conditions, for instance, cloudiness and obscurity. Existing image dehazing systems are chiefly in perspective on dark channel prior. Since the dark channel isn`t reasonable for sky districts, a sky division and zone wised medium transmission based image dehazing methodology is proposed in this paper. Directly off the bat, sky areas are separated by quad-tree part based segment pixels area. By then, a medium transmission estimation methodology for sky locales is proposed in perspective on shading trademark view of sky areas. The medium transmission is then isolated by an edge sparing guided channel. Finally, in light of the assessed medium transmission, the hazed images are reestablished. Exploratory results demonstrate that the execution of the proposed procedure is better than that of existing methods. The reestablished image is progressively ordinary, particularly in the sky areas.